Konflikt w procesie zarządzania przedsiębiorstwem - Wołoszyn, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The aim of the article is to present the essence of conflict and its role in process of enterprise management. It presents essence of conflict in work and reasons and result of conflict. It describe conceptual manners of solving of conflicts but especially basic styles of their arbitration (fight, submission, avoidance, compromise, cooperation) and its efficiency in managerial work. It underline role of chief in balancing and coordinating of interest of employee and managements in conflicts